PENGARUH PEMBELAJARAN BERBASIS STEAM (SCIENCE, TECHOLOGY, ENGINEERING, ART AND MATHEMATICS) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA - Salsabilla, Aqilla; Anwar; Muhammad Zaki (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2025)
The purpose of this study was to determine significant differences in mathematical problem-solving abilities between students participating in STEAM-based learning and students participating in conventional learning in grade ten of SMA Negeri 2 Patra Nusa. This study used a quantitative quasi-experimental approach with a posttest-only control group design. The population was all 113 grade ten students of SMA Negeri 2 Patra Nusa Manyak Payed in the 2024/2025 academic year. Sampling was conducted using simple random sampling, with class X MIA 1 as an experimental class and class X MIA 2 as the control class, each with 25 students. The research instrument was a descriptive test on quadratic functions. The results of the independent sample t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between the mathematical problem-solving abilities of students in the experimental and control classes. This research can be expanded by examining the effect of STEAM-based learning on other elements of the mathematical process.